1971
DOI: 10.1042/bj1250329
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control mechanisms in mammalian systems. Involvement of adenosine 3′:5′-cyclic monophosphate in androgen action

Abstract: 1. The ability of exogenously administered cyclic AMP (adenosine 3':5'-monophosphate) to exert andromimetic action on certain carbohydrate-metabolizing enzymes was investigated in the rat prostate gland and seminal vesicles. 2. Cyclic AMP, when injected concurrently with theophylline, produced marked increases in hexokinase, phosphofructokinase, glyceraldehyde phosphate dehydrogenase, pyruvate kinase, and two hexose monophosphate-shunt enzymes, as well as alpha-glycerophosphate dehydrogenase activity in access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1973
1973
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 36 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…It was reported that cAMP analogues inhibited the expression of mRNAs for RARo, -, and -y in F9 teratocarcinoma cells [29]. Since testosterone had been reported to stimulate adenyl cyclase activity in prostate glands of castrated rats [30], and cAMP levels in testes of hypophysectomized rats [31] and in rat seminal vesicles cultured in vitro [32], the suppression of RARy mRNA following testosterone administration may result from an increase of testicular cAMP. The increase in the RARa mRNA, on the other hand, perhaps reflects the net balance between the putative cAMP-mediated inhibitory effect and certain unidentified stimulatory mechanisms that apparently were absent or less effective in the expression of RARy mRNA.…”
Section: Discussionmentioning
confidence: 96%
“…It was reported that cAMP analogues inhibited the expression of mRNAs for RARo, -, and -y in F9 teratocarcinoma cells [29]. Since testosterone had been reported to stimulate adenyl cyclase activity in prostate glands of castrated rats [30], and cAMP levels in testes of hypophysectomized rats [31] and in rat seminal vesicles cultured in vitro [32], the suppression of RARy mRNA following testosterone administration may result from an increase of testicular cAMP. The increase in the RARa mRNA, on the other hand, perhaps reflects the net balance between the putative cAMP-mediated inhibitory effect and certain unidentified stimulatory mechanisms that apparently were absent or less effective in the expression of RARy mRNA.…”
Section: Discussionmentioning
confidence: 96%
“…We assume that this is the general case for all the tissues that are metabolically dependent on androgens; however, it is also possible that in some instances characteristics of the cell membrane determine the extent of entry. In this respect it is important to recall the involvement of cyclic AMP in androgen action in the secondary sexual tissues of the rat (Rosenfeld & O'Malley, 1970;Singhal et al 1971 ;Mangan, Pegg & Mainwaring, 1973). Once the androgen is inside the cell, it is subjected to extensive metabolic conversions.…”
Section: General Remarksmentioning
confidence: 99%
“…The present study throws doubt on part of this interesting hypothesis, since we failed to elicit a rise in uterine cyclic AMP production by oestradiol treatment, and have also failed to demonstrate any increase in uterine protein kinase activity within 4 h of a sub¬ cutaneous injection of 5 fig oestradiol-11 ß in immature rats (unpublished observa-37-2 tions). Singhal & Lafreniere (1972) propose, on different grounds (see Introduction), that cyclic AMP plays an important role in triggering all the known metabolic effects of oestrogens on the uterus. Our findings do not support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…These results led Szego & Davis (1967), Szego (1972 and Singhal & Lafreniere (1972) to propose that the adenyl cyclase-cyclic AMP system of the cell membrane, and possibly /i-adrenergic receptors (Szego & Davis, 1969a), may be implicated in the mediation of the earliest effects of oestradiol on the uterus. On the other hand, it is widely believed that the primary interaction of oestradiol in target organs is with a cytoplasmic receptor protein (Noteboom & Gorski, 1965;King & Gordon, 1966;Jensen, Suzuki, Kawashima, Stumpf, Jungblut & DeSombre, 1968).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation